2021
DOI: 10.1186/s13000-021-01105-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel tumor suppressor ASMTL-AS1 regulates the miR-1228-3p/SOX17/β-catenin axis in triple‐negative breast cancer

Abstract: Background Triple-negative breast cancer (TNBC) is a special type of breast cancer that lacks effective therapeutic targets. There is a significant need to clarify its pathogenesis, so as to bring new targeted approaches for TNBC management. Here, we identified a long-non coding RNA (lncRNA) ASMTL-AS1 that linked to TNBC development and progression. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot assays were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, its role in cancer may be context-dependent. For example, in breast cancer, the poor expression of ASMTL-AS1 was tightly linked with advanced stage and poor prognosis, and ASMTL-AS1 overexpression might inactivate the oncogenic Wnt/β-catenin pathway and subsequently retard breast cancer progression in vitro and in vivo [ 11 ]. In papillary thyroid carcinoma, ASMTL-AS1 exerts tumor-suppressive functions by suppressing the proliferative and metabolic phenotypes of tumor cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role in cancer may be context-dependent. For example, in breast cancer, the poor expression of ASMTL-AS1 was tightly linked with advanced stage and poor prognosis, and ASMTL-AS1 overexpression might inactivate the oncogenic Wnt/β-catenin pathway and subsequently retard breast cancer progression in vitro and in vivo [ 11 ]. In papillary thyroid carcinoma, ASMTL-AS1 exerts tumor-suppressive functions by suppressing the proliferative and metabolic phenotypes of tumor cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple mechanisms by which lncRNAs interfere with gene expression, the competing endogenous RNA (ceRNA) mechanism has always been a research hotspot. ASMTL-AS1 has been reported to act as a tumor suppressor in thyroid carcinoma [ 10 ] and breast cancer [ 11 ] due to its ceRNA activity. However, a recent study showed that ASMTL-AS1 is highly expressed in HCC and favors malignant tumor phenotypes through miR-342-3p/YAP (Yes1-associated transcriptional regulator) signaling [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the level of ASMTL-AS1 in gastric cancer tissues and cells was quantitatively assessed by RT-qPCR. Previously, ASMTL-AS1 was reported to be significantly downregulated in triple-negative breast cancer and bladder cancer tissues [ 13 , 25 ]. Similarly, ASMTL-AS1 was significantly decreased in gastric tissues and cells when compared with the normal ones.…”
Section: Discussionmentioning
confidence: 99%
“…Because ASMTL-AS1 and miR-1270 were negatively correlated in expression level, miR-1270 mimic can reduce the fluorescence intensity of the wide-type ASMTL-AS1, and ASMTL-AS1 could pull down miR-1270. The ceRNA role of ASMTL-AS1 was also found in osteosarcoma with miR-342-3p, hepatocellular carcinoma with miR-1343-3p, and breast cancer by sponging miR-1228-3p [ 12 , 13 , 31 , 32 ]. Given the dysregulation of ASMTL-AS1 and miR-1270 in gastric cancer, whether ASMTL-AS1/miR-1270 regulatory loop affects the cell biological behaviors of gastric cells was further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation